INTERDEPENDÊNCIA ORÇAMENTO PÚBLICO E GARANTIA DO DIREITO À EDUCAÇÃO DE ESTUDANTES COM DEFICIÊNCIA: UMA ANÁLISE DA TERCEIRIZAÇÃO DO ATENDIMENTO EDUCACIONAL ESPECIALIZADO - Oliveira, Gildásio Macedo de (2021)
This thesis aims to analyze the interdependence of the public budget and the guarantee of the right to education for children and adolescents with disabilities, in outsourcing the AEE, in the 2016-2019 budget cycle. To do so, a descriptive research of a predominantly qualitative nature is carried out with the use of document analysis and interviews. As a data source, the state public budget was used as a guiding principle. The open data were extracted from the transparency portal of the state of Espírito Santo. In parallel, the Pluriannual Plan (PPA 2016- 2019) was consulted; Budget Guidelines Laws (LDO); Annual Budget Laws (LOA); Reports on the Programmatic Execution of the State Budget from 2016 to 2019; Summary Reports on Budget Execution (RREO) from 2016 to 2019; Report of public hearings for the construction of the PPA; Technical Budget Manuals (MTO) of the state of Espírito Santo and the Union; Official Gazette of Espírito Santo (DIOES); institutional websites and legislation that support Special Education. In addition, the microdata from the Basic Education school census of the National Institute of Educational Studies and Research Anísio Teixeira (Inep) was used to access enrollment indicators. To complement the informational universe, we focused on data from two large specialized philanthropic institutions, Apae de Vitória and Apae da Serra. Their pedagogical proposals were analyzed; the content of reports on services provided from September 2018 to September 2019; and, the data from the face-to-face interviews conducted with the mothers of students from the state school system who used the private AEE of these institutions. The data were analyzed through the lens of Norbert Elias' figurational sociology (1897-1990). From this theoretical-methodological perspective, it is understood that there is no "I" without us, and that society is a social and dynamic process of dependencies and interdependencies. For a better understanding of the social game that announces school inclusion, networks of interdependence by the marks left in the public budget are sought. For a critical analysis of the financing of the AEE's outsourcing policy, budget indicators of direction, magnitude and scope of social spending were used. It is observed that the outsourcing of AEE evokes individual interests as a subterfuge to the challenge of sharing human experience, having the interest of constituting itself as a parallel (“essential”) service to schooled education, generating possibilities for the private philanthropic sector without non-profit purposes dispute pari passu public educational resources, subordinating the public sphere to private philanthropic assistance interests, contributing directly to the precariousness of teaching in public schools. It is, therefore, an ingenious mechanism to promote philanthropy, of dubious legality, which “maneuvers'' the filtering of Fundeb's 2nd registration; it aims at the financial sustainability of the institutions, which do not want the instability of the public subsidy. Finally, the AEE’s right to choose local argument is camped out because a large portion of the special education students is directed to specialized private institutions, which gain relevance due to the consent of the state of Espírito Santo, which ceases to invest directly in public sphere.